Snapshots of waveforms in multitrack digital recordings:an asset for the assessment of simultaneous interpreting - Torres-Díaz, María Gracia; Ghignoli, Alessandro (My University, 2014)
Una nueva herramienta para la evaluación de los intérpretes que se forman en la modalidad de simultánea.
Keywords: Traducción; Digital recordings; Simultáneous interpreting